Different adaptive patterns of wheat with different drought tolerance under drought stresses and rehydration revealed by integrated metabolomic and transcriptomic analysis - Lv, Liangjie; Chen, Xiyong; Li, Hui; Huang, Jinan; Liu, Yuping; Zhao, Aiju (Frontiers in Plant Science, 2022)
Wheat as a staple food crop is enduring ever-frequent intermittent and changing drought with the climate change. It is of great significance to highlight the adaptive approaches under such variable conditions at multiple levels to provide a comprehensive understanding of drought tolerance and facilitate the genetic breeding of wheat. Therefore, three wheat lines with different drought tolerance (drought tolerant mutant Mu>common wheat CK> drought susceptible mutant mu) were analyzed under moderate and severe drought stresses as well as rehydration. Samples were subjected to transcriptomic and metabolomic profiling in combination with physiological and biochemical determination. The moderate drought stress rendered 198 and 115 differentially expressed metabolites (DEMs) in CK and Mu, respectively. The severe drought stress rendered 166, 151 and 137 DEMs in CK, Mu and mu, respectively. The rehydration rendered 150 and 127 DEMs in CK and Mu. 12,557 and 10,402 differentially expressed genes (DEGs) were identified for CK and Mu under moderate drought stress, respectively. 9,893, 7,924, and 9,387 DEGs were identified for CK, Mu, and mu under severe drought stress, respectively. 13,874 and 14,839 were identified in CK and Mu under rehydration, respectively. Metabolomics results showed that amino acid was the most differentially expressed metabolites, followed by phenolic acids. Flavonoids played an important role in drought tolerance. Most enriched pathways under drought included biosynthesis of secondary metabolites, metabolic pathways and photosynthesis. Metabolites and genes involved in osmotic regulation, antioxidase activities, and ABA signaling were more enriched in Mu than in CK and mu. Various drought-responsive genes and metabolites in Mu showed different trends with those in CK and mu. Increased amino acids biosynthetic capability and ROS scavenging ability resulted from higher antioxidase activities and increased flavonoids may be the mechanisms underlying the drought tolerance characteristic of Mu. Recovery from reversible ROS damage and rapid amino acid biosynthesis may contribute to the rapid recovery of Mu. The present study provides new insights for mechanisms of wheat under complex drought conditions.